A CSR project - beach clean-up project at Port Dickson - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2023)
On the 8th of July 2023, a group of 14 MBA students (AA7002BF) organized a CSR program in collaboration with two companies; AABIOS Design Malaysia) Sdn Bhd and RFL Petrolab Sdn Bhd. The program was held at Pantai Cermin and Pantai Tanjung Biru, Port Dickson, Negeri Sembilan. It is an initiative for the OPM770 Operations Management course that encourages active learning, such as the beach cleaning project, to understand environmental issues and the severity of pollution due to negligence in business operations. One of the course’s learning outcomes is to instil good values, ethics, and professionalism. Associate Professor Dr Hadijah Iberahim supervised the CSR program. The purpose of the CSR activity in Port Dickson was to foster a sense of social responsibility and environmental protection among the participants. The experiential learning program, which took up 3 hours at the site, successfully removed four trash bags, approximately 70 kgs. All the participants shared very satisfying feelings about their first volunteering experience, collecting plastic bottles, tin cans, straws, shoes, food wrappers, plastic grocery bags, cigarette butts and others. The beach clean-up is a great way to make the ocean safe and pleasant for animals and people. It also reminds the importance of avoiding littering that will harm the ecosystem and serenity of beaches. Nevertheless, the program was not merely meant to enjoy beautiful clean beaches and take a break from stressful routines, but it helped to build teamwork, do good for the environment, and live a sustainable life. Through active participation in garbage collection and understanding the detrimental effects of waste on coastal ecosystems, the participants were motivated to become catalysts for positive change in the communities.